2006
DOI: 10.1597/04-156.1
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hoffmeister's “Genetically Determined Predisposition to Disturbed Development of the Dentition” in Patients with Cleft Lip and Palate

Abstract: These findings support the hypothesis that clefting is part of a complex malformation associated with other dental anomalies resulting from disturbed development of the dentition. Patients with clefts are also likely to present other deficiencies of dental development and tooth eruption in both dentitions, even in regions not affected by the cleft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 22 publications
5
30
0
3
Order By: Relevance
“…Our estimates captured only erupted supernumerary teeth, due to the lack of radiographs. Similar to previous studies, however, we found more supernumerary teeth in individuals with cleft lip compared with other clefts (Stahl et al 2006;Riis et al 2014). Finally, our study also captured significant increases in dental displacements and a trend for increased rotations in the maxillary primary and permanent dentitions of our case probands, similar to previous studies (Letra et al 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our estimates captured only erupted supernumerary teeth, due to the lack of radiographs. Similar to previous studies, however, we found more supernumerary teeth in individuals with cleft lip compared with other clefts (Stahl et al 2006;Riis et al 2014). Finally, our study also captured significant increases in dental displacements and a trend for increased rotations in the maxillary primary and permanent dentitions of our case probands, similar to previous studies (Letra et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…found that dental anomalies increase with cleft severity (Stahl et al 2006;Letra et al 2007;Aizenbud et al 2011). Mutations in genes influencing both palatogenesis and dental development could also partly account for the greater prevalence of dental anomalies in individuals with clefts.…”
mentioning
confidence: 99%
“…It has been proposed that clefting is part of a complex malformation that can be associated with dental anomalies resulting from the disturbed development of the dentition [Stahl et al, 2006]. In that context, we have shown that dental anomalies outside the cleft area could be used as additional features for the generation of more sophisticated cleft subphenotypes [Letra et al, 2007].…”
mentioning
confidence: 68%
“…Os indivíduos com fissuras labiopalatinas, além de grave problema estético, apresentam distúrbios funcionais severos, de forma que, se esta deformidade não for tratada incidência de anomalias dentárias do que indivíduos sem fissuras e ainda, que a gravidade das anomalias dentárias parece estar relacionada à gravidade das fissuras labiopalatinas, principalmente quando se trata de fissura de lábio isolada (Adams e Niswander 1967, Schroeder e Green 1975, Larson et al 1998, Eerens et al 2001, Stahl et al 2006, Aizenbud et al 2010). …”
Section: Fissura Labiopalatinaunclassified
“…2001, Stahl et al 2006, Aizenbud et al 2010. Defeitos na formação do esmalte dentário são frequentes em indivíduos com fissura labiopalatina e a sua intensidade parece depender da gravidade da fissura.…”
Section: Estudo Genético Da Mutação Do Gene Amelx Na Malformação Dentunclassified